Divinfood, NUCs and agrobiodiversity – Agile Food Design and Living Labs for sustainable innovation - Sonia Massari; Francesca Galli; Luca Colombo; Gabriele Goretti (Agathón)
This article explores the role of agile food design as a catalyst for innovation in agri-food systems, starting from the European project Divinfood, which aims to enhance underutilised agrobiodiversity, such as white lupin, through co-creation methodologies. The transdisciplinary approach, which combines scientific research and design, facilitates the creation of sustainable solutions for ecological transition. Through Living Labs, scenario-based design enables the generation of new synergies among agri-food supply chain actors, promoting the integration of creative skills to respond to sustainability challenges. The study highlights how collaborative and agile food design can contribute to a more inclusive, sustainable, and resilient agri-food system, in line with the Sustainable Development Goals of the 2030 Agenda.